Carbon fluoride thick electrode, preparation method thereof and primary battery

By optimizing the slurry formula and multiple coating methods, a carbon fluoride thick electrode with pressure resistance and not easy to crack was prepared, which solved the problems of prone to cracking and deterioration of dynamic characteristics of traditional electrodes, and achieved efficient improvement of battery performance.

CN119852301AActive Publication Date: 2025-04-18LIGONG PEGASUS (BEIJING) TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510024745.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-18
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

The traditional wet coating method prepares carbon fluoride thick electrodes with easy cracking and falling off, resulting in limited area capacity, deterioration of kinetic characteristics, and reduced material utilization.

Method used

The carbon fluoride thick electrode is prepared by optimizing the slurry formula and multiple coatings. The mesh metal current collector is used as the skeleton to gradually increase the coating thickness to form a step-by-step structure to enhance the mechanical properties and dynamic characteristics of the electrode.

Benefits of technology

The prepared carbon fluoride thick electrode has a voltage resistance and is not prone to cracking. The utilization rate of active materials reaches more than 94%, showing an ultra-high area specific capacity and volume specific capacity, which significantly improves the performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852301A_ABST
    Figure CN119852301A_ABST
Patent Text Reader

Abstract

According to the carbon fluoride thick electrode, the preparation method thereof and the primary battery provided by the invention, the carbon fluoride thick electrode is obtained by optimizing a slurry formula and coating for multiple times, the method is simple, convenient and feasible, the requirement on equipment is low, and the obtained thick electrode is pressure-resistant, is not easy to crack, and can be applied to the field of secondary batteries. And the lithium carbon fluoride battery composed of the material and lithium metal shows ultrahigh area specific capacity, and the material utilization rate is 94% or above. The electrode with any thickness can be obtained through a multi-time coating method, the manufacturing method is simple, and a battery manufactured by matching the obtained carbon fluoride thick electrode with an alkali metal negative electrode has the advantages of high surface capacity and high volume specific capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of primary batteries, and in particular relates to a fluorinated carbon thick electrode and a preparation method thereof, and a primary battery. Background Art

[0002] Carbon fluoride / lithium battery is a primary battery with high specific energy, wide operating temperature range, low self-discharge, and long storage life. It is widely used in various civilian and military equipment. However, due to the limited reserves of lithium resources on the earth, a lot of research has been focused on the research and development of sodium and potassium ion batteries of the same family. With the extensive research on new battery systems conducted by the scientific community in recent years, it has been found that carbon fluoride can react electrochemically with sodium and potassium ions, which shows that carbon fluoride materials can be matched with metallic sodium and potassium as a new type of primary battery.

[0003] With the widespread application and popularization of electronic devices, the market demand for high specific energy primary batteries is becoming more and more urgent, and the traditional coated thin electrodes or other methods of preparing powder electrodes can no longer meet the needs. Therefore, it is urgent to develop a new electrode preparation technology to obtain thick carbon fluoride electrodes. In addition, although carbon fluoride / sodium and carbon fluoride / potassium batteries have achieved rich results in theoretical research, they still require reasonably designed carbon fluoride electrodes to be compatible with the corresponding alkali metals to achieve practical application.

[0004] Patent document CN112201770A discloses a method for preparing a fluorocarbon electrode, which includes: 1) coating an electrode slurry on a current collector and drying it to obtain a layer of electrode membrane; 2) repeating the operation of coating the electrode slurry on the electrode membrane obtained in the previous operation and drying it at least once to obtain the electrode sheet, thereby increasing the active material loading per unit area of ​​the current collector and improving the energy density of the electrode sheet.

[0005] It can be seen that the commonly used method to increase energy density is to achieve high area capacity by thickening the electrode. A thicker electrode means a higher utilization rate of the space inside the battery, thereby obtaining a higher energy density and reducing costs. However, for the preparation of thick electrodes, as the thickness of the electrode increases, it is easier to crack and fall off, especially for traditional wet-coated electrodes. This is also the reason why the area capacity of wet-coated electrodes is limited. Secondly, the increase in electrode thickness leads to the deterioration of its kinetic properties, making it impossible for the material to fully react, resulting in a decrease in the utilization rate of the active material.

[0006] Therefore, a new electrode preparation process is needed to develop high-performance carbon fluoride thick electrodes to meet the requirements of alkali metal primary batteries for improving energy density. Summary of the invention

[0007] In view of the above problems, the present invention aims to provide a preparation method and application of a thick carbon fluoride electrode. The present invention obtains a thick carbon fluoride electrode by optimizing the slurry formula and performing multiple coatings. The method is simple and feasible, has low equipment requirements, and the obtained thick electrode is pressure-resistant and not easy to crack. The lithium carbon fluoride battery composed of the electrode and lithium metal exhibits an ultra-high area specific capacity, and the material utilization rate is above 94%.

[0008] In order to achieve the above object, the present invention provides a method for preparing a fluorinated carbon thick electrode, the preparation method comprising the following steps: (1) mixing carbon fluoride active material, binder, conductive agent 1 and conductive agent 2 in a certain proportion, adding solvent and stirring to form electrode slurry; (2) coating the slurry described in step (1) on one or both sides of a mesh metal current collector; (3) After coating, the electrode is dried at a constant temperature until the electrode is semi-solid to obtain an electrode sheet, and then the electrode slurry is coated on the electrode sheet obtained in the previous operation and dried at a constant temperature until the electrode is semi-solid. The above operation is repeated. After the last coating is completed and the electrode is dried at a constant temperature to a semi-solid state, it is transferred to an oven for vacuum drying to obtain a fluorinated carbon thick electrode. The electrode sheet is coated at least four times. Furthermore, during the coating process, the coating thickness increases in a step-by-step manner. By increasing the thickness of the coating layer in a step-by-step manner during the coating process, not only can the problem of cracking and falling off of the electrode piece as the electrode thickness increases be avoided, but this process can also increase the dynamic characteristics of the electrode piece, allowing the material in the electrode to fully react, thereby improving the utilization rate of the active material and improving the performance of the battery.

[0009] Furthermore, the fluorinated carbon active substance in step (1) includes one or more of fluorinated graphite, fluorinated carbon nanotubes, fluorinated graphene, fluorinated carbon fibers, fluorinated carbon nanodisks, and fluorinated coke.

[0010] Furthermore, it is characterized in that the binder is polyvinylidene fluoride (PVDF) with a molecular weight of 1000 to 10000.

[0011] Furthermore, it is characterized in that the conductive agent 1 in step (1) includes one or more of multi-walled carbon nanotubes (MWCNT), single-walled carbon nanotubes (SWCNT), vapor-grown carbon fibers (VGCF), and carbon nanofibers (CNF); the conductive agent 2 in step (1) includes one or more of superconducting carbon black, acetylene black, Ketjen black, and conductive graphite balls. The conductive agent 1 is a one-dimensional structure, and the conductive agent 2 is a zero-dimensional structure. The one-dimensional conductive agent 1 can form a network structure in the active material layer, and the zero-dimensional conductive agent 2 is filled in the gaps of the network structure composed of the one-dimensional material, so that the entire active material can be surrounded by the conductive agent, thereby improving the conductivity of the electrode and further improving the performance of the electrode; Furthermore, in step (1), the mass ratio of carbon fluoride, adhesive, conductive agent 1, and conductive agent 2 is (80-96)%: (1-14)%: (1-14)%: (1-14)%; and the solid content of the slurry in step (1) is 25%-50%.

[0012] Furthermore, the mesh metal current collector in step (2) is one of stainless steel mesh, nickel mesh, titanium mesh, copper mesh, aluminum mesh, tungsten mesh, molybdenum mesh, zirconium mesh or platinum mesh.

[0013] Furthermore, in step (3), the constant temperature drying temperature ranges from 25 to 50°C; and the vacuum drying temperature ranges from 50 to 80°C.

[0014] Furthermore, the coating method includes one or more of spraying, scraping and spin coating.

[0015] The present invention also provides a primary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; characterized in that the positive electrode sheet is a fluorinated carbon thick electrode sheet prepared by the above method, and the negative electrode is one of metal lithium, sodium and potassium.

[0016] Compared with the prior art, the present invention has the following advantages: 1. Improvements are made on the traditional coating method, with simple preparation. The thickness of the produced electrode can be changed as needed (200µm~3000µm); the slurry composition and ratio can also be optimized according to the required discharge characteristics; single-sided or double-sided coating can be selected according to the battery configuration, which has good flexibility; since the mesh current collector acts as a skeleton, the prepared electrode has good mechanical properties. At the same time, the electrode is heated to a semi-solid state during the coating process, and is not completely dried. Multiple coatings are performed on the basis of the semi-solid state, so that the finally prepared electrode is not easy to crack, and the vertical pressure will not be damaged like the traditional powder thick electrode.

[0017] 2. During the coating process, the coating thickness increases in a step-by-step manner. By increasing the thickness of the coating layer in a step-by-step manner during the coating process, not only can the problem of cracking and falling off of the electrode piece as the electrode thickness increases be avoided, but this process can also increase the dynamic characteristics of the electrode piece, allowing the material in the electrode to fully react, thereby improving the utilization rate of the active material and improving the performance of the battery.

[0018] 3. By combining a conductive agent 1 with a one-dimensional structure and a conductive agent 0 with a dimensional structure, the one-dimensional conductive agent 1 can form a network structure in the active material layer, and the 0-dimensional conductive agent 2 is filled in the gaps in the network structure composed of the one-dimensional material to construct a three-dimensional conductive network, so that the active material in the electrode can be surrounded by the conductive agent as a whole, thereby improving the conductivity of the electrode and further improving the performance of the electrode. The final thick electrode has extremely high area specific capacity and volume specific capacity. If it is made into a lithium fluoride carbon battery, it can obtain a volume specific capacity that is more than twice that of a commercial battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is an appearance diagram of the thick electrode provided in Examples 1-5.

[0020] Figure 2 This is the discharge curve of Example 1.

[0021] Figure 3 This is the discharge curve of Example 2.

[0022] Figure 4 This is the discharge curve of Example 3.

[0023] Figure 5 This is the discharge curve of Example 4.

[0024] Figure 6 This is the discharge curve of Example 5.

[0025] Figure 7 This is the discharge curve of comparative example 1.

[0026] Figure 8 This is the discharge curve of comparative example 2.

[0027] Fig. 9 This is the discharge curve of comparative example 3.

[0028] Fig.10 This is the appearance of the electrode during the coating and drying process of Comparative Example 3. DETAILED DESCRIPTION

[0029] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods and accompanying drawings, but the implementation methods of the present invention are not limited thereto.

[0030] In the present invention, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.

[0031] Example 1 Graphite fluoride, polyvinylidene fluoride (Mw=5130), multi-walled carbon nanotubes, and Super P were mixed and ground evenly in a ratio of 90:6:2:2, and N-methylpyrrolidone solvent was added and stirred to form a slurry, wherein the solid content of the slurry was 37%. The slurry was coated on a flat 100-mesh stainless steel mesh using a scraper, and dried at a constant temperature of 35°C until semi-solid, and then the single-sided coating with active material and the drying process were repeated 4 times, and the scraper spacing used for coating was 1.5mm, 1.5mm, 2mm, and 2mm, respectively. After the last drying to semi-solid, it was transferred to an oven, dried at 60°C for 12h, and then punched into a disc electrode with a diameter of 1cm, and placed in a vacuum oven for standby use. The above disc electrode was assembled into a button cell with metal lithium for testing. The isolation membrane used was a PP diaphragm, and the electrolyte was a 1M LiBF4 dissolved in a mixed solution of ethylene glycol dimethyl ether and propylene carbonate.

[0032] Example 2 Graphite fluoride, polyvinylidene fluoride (Mw=5130), multi-walled carbon nanotubes, and Super P were mixed and ground evenly in a ratio of 90:6:2:2, and N-methylpyrrolidone solvent was added and stirred to form a slurry, wherein the solid content of the slurry was 40%. Use a scraper to apply the slurry on a flat 80-mesh aluminum mesh, dry it at a constant temperature of 35°C to a semi-solid state, and then repeat the single-side coating and drying process with active material for a total of 4 times. The scraper spacing used for coating was 1.5mm, 1.5mm, 2mm, and 2mm, respectively. After the last drying to a semi-solid state, it was transferred to an oven, dried at 60°C for 12h, and then punched into a disc electrode with a diameter of 1cm, and put it in a vacuum oven for standby use. The above disc electrode was assembled into a button cell with metal lithium for testing. The isolation membrane used was a PP diaphragm, and the electrolyte was 1 MLiBF4 dissolved in a mixed solution of ethylene glycol dimethyl ether and propylene carbonate.

[0033] Example 3 Graphene fluoride, polyvinylidene fluoride (Mw=5130), single-walled carbon nanotubes, and Super P were mixed and ground in a ratio of 92:4:2:2, and N-methylpyrrolidone solvent was added and stirred to form a slurry, wherein the solid content of the slurry was 40%. The slurry was coated on a flat 80-mesh aluminum mesh using a scraper, and dried at a constant temperature of 35°C until semi-solid, and then the single-sided coating with active material and the drying process were repeated 4 times. The spacing of the scraper used for coating was 1.5mm, 1.5mm, 2mm, and 2mm, respectively. After the last drying to semi-solid, it was transferred to an oven, dried at 60°C for 12h, and then punched into a disc electrode with a diameter of 1cm, and put into a vacuum oven for standby use. The above disc electrode was assembled into a button cell with metal lithium for testing. The isolation membrane used was a PP diaphragm, and the electrolyte was a 1M LiBF4 dissolved in a mixed solution of ethylene glycol dimethyl ether and propylene carbonate.

[0034] Example 4 Graphite fluoride, polyvinylidene fluoride (Mw=5130), multi-walled carbon nanotubes, and Super P were mixed and ground in a ratio of 90:6:2:2, and N-methylpyrrolidone solvent was added and stirred to form a slurry, wherein the solid content of the slurry was 40%. The slurry was coated on a flat aluminum mesh using a scraper, and dried at a constant temperature of 35°C until it was semi-solid, and then the single-side coating with active material and the drying process were repeated 4 times. After a wet solid surface was formed, the coating and drying process on the other side were repeated 4 times. The spacing of the scraper used for coating was 1.5mm, 1.5mm, 2mm, and 2mm, respectively. After the last drying to a semi-solid state, it was transferred to an oven and dried at 60°C for 12 hours to obtain a thick electrode coated on both sides, which was cut into 0.8×0.8cm pole pieces with pole ears and placed in a vacuum oven for standby use. The above-mentioned disc electrode and metallic lithium were assembled into a button cell for testing. The isolation membrane used was a PP separator and the electrolyte was a mixed solution of 1 M LiBF4 dissolved in ethylene glycol dimethyl ether and propylene carbonate.

[0035] Example 5 The difference between this embodiment and embodiment 2 is that the finished thick electrode of this embodiment is assembled into a button cell with metallic sodium, the isolation membrane used is a GF / A glass fiber membrane, and the electrolyte is 1 M NaPF6 dissolved in a mixed solution of ethylene glycol dimethyl ether and propylene carbonate.

[0036] Comparative Example 1 The difference between this comparative example and Example 2 is that the electrode material is composed of graphite fluoride, polyvinylidene fluoride (Mw=5130), and multi-walled carbon nanotubes in a ratio of 90:6:4, and the other parameters are the same as those in Example 2.

[0037] Comparative Example 2 The difference between this comparative example and Example 2 is that the electrode material is composed of graphite fluoride, polyvinylidene fluoride (Mw=5130), and Super P in a ratio of 90:6:4, and the other parameters are the same as those in Example 2.

[0038] Comparative Example 3 The difference between this comparative example and Example 2 is that after each coating of the slurry, the electrode is dried thoroughly before subsequent coating.

[0039] Implementation Effect Figure 1 (a, b) front and back pictures of the thick electrode in Example 1; (c, d) front and back pictures of the thick electrode in Examples 2 and 5; (e, f) front and back pictures of the thick electrode in Example 3; (g) front and back pictures of the thick electrode in Example 4. The thickness of the thick electrode prepared in Examples 1-4 is 1400-1600 µm, and the appearance of the thick electrode in Examples 1-6 is as follows: Figure 1 As shown, it can be seen that the thick electrode in the embodiment has good mechanical properties and is not easy to crack and damage; Fig.10 As shown, Comparative Example 3 did not fully adopt the method of the present invention, resulting in cracking of the electrode during the drying process. It can be seen from Example 2 and Comparative Examples 1-2 that it is impossible to construct a three-dimensional network conductive structure using only one-dimensional materials or 0-dimensional carbon materials, which ultimately causes the electrochemical performance of the battery to deteriorate. The discharge data corresponding to the embodiments are shown in Tables 1 and Figure 2-6 As shown. It can be seen that the fluorinated carbon thick electrode prepared according to the method provided by the present invention exhibits extremely high area capacity, with a single-sided coating capacity of 100 mAh / cm 2 Double-sided coating can double to 200 Ah / cm 2 As mentioned above, the utilization rate of active materials is generally above 94%, which has good economy. Secondly, the fluorinated carbon thick electrode is well compatible with the alkali metal negative electrode (Comparative Examples 2 and 5), and can be used to assemble various alkali metal primary batteries.

[0040] Table 1 Discharge data of fluorinated carbon thick electrode batteries between different examples

[0041] The above are only exemplary embodiments of the present disclosure, and the scope of the present disclosure cannot be limited thereto. That is, any equivalent changes and modifications made according to the teachings of the present disclosure are still within the scope of the present disclosure. After considering the disclosure of the specification and the truth of practice, it will be easy for those skilled in the art to think of other embodiments of the present disclosure. This application is intended to cover any variation, use or adaptive change of the present disclosure, which follows the general principles of the present disclosure and includes common knowledge or customary techniques in the technical field that are not recorded in the present disclosure.

Claims

1. A method for preparing a fluorinated carbon thick electrode, characterized in that: The preparation method comprises the following steps: (1) mixing carbon fluoride active material, binder, conductive agent 1 and conductive agent 2 in a certain proportion, adding solvent and stirring to form electrode slurry; (2) coating the slurry described in step (1) on one or both sides of a mesh metal current collector; (3) After coating, the electrode is dried at a constant temperature until the electrode is semi-solid to obtain an electrode sheet, and then the electrode slurry is coated on the electrode sheet obtained in the previous operation and dried at a constant temperature until the electrode is semi-solid. The above operation is repeated. After the last coating is completed and the electrode is dried at a constant temperature to a semi-solid state, it is transferred to an oven for vacuum drying to obtain a fluorinated carbon thick electrode. The electrode sheet is coated at least four times.

2. The method for preparing a fluorinated carbon thick electrode according to claim 1, characterized in that: During the coating process, the coating thickness increases in a step-by-step manner.

3. The method for preparing a fluorinated carbon thick electrode according to claim 1, characterized in that: The fluorinated carbon active material in step (1) includes one or more of fluorinated graphite, fluorinated carbon nanotubes, fluorinated graphene, fluorinated carbon fibers, fluorinated carbon nanodisks, and fluorinated coke.

4. The method for preparing a fluorinated carbon thick electrode according to claim 1, characterized in that: The binder is polyvinylidene fluoride (PVDF) with a molecular weight of 1000 to 10000.

5. The method for preparing a fluorinated carbon thick electrode according to claim 1, characterized in that: The conductive agent 1 in step (1) includes one or more of multi-walled carbon nanotubes (MWCNT), single-walled carbon nanotubes (SWCNT), vapor grown carbon fibers (VGCF), and carbon nanofibers (CNF); the conductive agent 2 in step (1) includes one or more of superconducting carbon black, acetylene black, Ketjen black, and conductive graphite balls.

6. The method for preparing a fluorinated carbon thick electrode according to claim 1, characterized in that: In step (1), the mass ratio of carbon fluoride, adhesive, conductive agent 1, and conductive agent 2 is (80-96)%: (1-14)%: (1-14)%: (1-14)%; and the solid content of the slurry in step (1) is 25%-50%.

7. The method for preparing a fluorinated carbon thick electrode according to claim 1, characterized in that: The mesh metal current collector in step (2) is one of stainless steel mesh, nickel mesh, titanium mesh, copper mesh, aluminum mesh, tungsten mesh, molybdenum mesh, zirconium mesh or platinum mesh.

8. The method for preparing a fluorinated carbon thick electrode according to claim 1, characterized in that: In step (3), the constant temperature drying temperature ranges from 25 to 50°C; the vacuum drying temperature ranges from 50 to 80°C.

9. The method for preparing a fluorinated carbon thick electrode according to claim 1, characterized in that: The coating method includes one or more of spray coating, scraper coating and spin coating.

10. A primary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; characterized in that: The positive electrode plate is a fluorinated carbon thick electrode plate prepared by the method according to any one of claims 1 to 9, and the negative electrode is one of metal lithium, sodium and potassium.

Citation Information

Patent Citations

  • Electrode plate, preparation method thereof and lithium battery

    CN112201770A

  • Preparation method of thick electrode with low solid-content slurry of lithium ion battery

    CN102969483A

  • Semi-dry forming process of high-power multi-layer chip capacitor

    CN114188157A

  • Thick electrode and preparation method and application thereof

    CN115207268A

  • Gradient carbon fluoride electrode and preparation method thereof

    CN115483366A